Effect of Ion Exchange Resin Functionality on Catalytic Activity and Leaching of Palladium Nanoparticles in Suzuki Cross‐Coupling Reactions. Issue 3 (19th December 2016) - Van Vaerenbergh, Beau; Lauwaert, Jeroen; Bert, Wim; Thybaut, Joris W.; De Clercq, Jeriffa; Vermeir, Pieter
Abstract: Macroporous ion exchange resin supported palladium nanoparticle (Pd‐NP) catalysts are prepared by an intermatrix synthesis. For the first time, the effect of resin functionality (weak acid, strong acid, strong base) on the NP size, their catalytic activity, and leaching is investigated in the Suzuki cross‐coupling of iodobenzene and phenylboronic acid. Whereas the smallest NPs (1.34 nm) are found in the thiol Ambersep GT74 resin, the sulfonic acid Lewatit K2629 and quaternary amine Lewatit MP500 OH resins resulted in NPs of a similar size (2.42 and 2.59 nm, respectively). Despite their smaller size, the NPs on Ambersep GT74 exhibited the lowest conversion (21.6 %), which is attributed to a too strong coordination of the NPs by the thiol groups. The conversions obtained by using Lewatit K2629 (76.8 %) and Lewatit MP500 OH (94.2 %) were considerably higher, the excellent performance of the latter catalyst being ascribed to the promoting effect of the hydroxyl groups on the transmetallation and reductive elimination steps in Suzuki cross‐coupling. No Pd leaching was observed when using Ambersep GT74 as the support, compared with Pd leaching amounting to 1.1 % and 4.8 % when using Lewatit MP500 OH and Lewatit K2629, respectively. Such low values indicate that ion exchange resins are ideal supports to stabilize the NPs. Particularly, the combination of high conversion and limited leaching on Lewatit MP500 OH opens up new perspectives for catalyzing Suzuki cross‐coupling with a heterogeneous catalyst. Abstract : A walk‐through of the functionality effects : Palladium nanoparticles (Pd‐NPs) stabilized by three different ion exchange resins were prepared and screened in the Suzuki cross‐coupling reactions.